Necessity and Possibility of transformation of polluted territories in safety systems - G. A. Sharovarov; Z. P. Miniouk (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers necessity and possibility of a transformation of polluted territories of Belarus, the Ukraine and Russia to ecologically-safe systems by radionuclides, actinoids and hot particles. The real possibility of the problem solution while applying special plants-hyper-accumulator is shown in the paper.